An analysis of citations of the University of the Philippines Institute of Library Science master's theses and special problems from 1990 to 1998 - Campañano, Theodore Joseph A. (1999)
This study used the process of citation analysis to investigate the characteristics of journal citations in 108 master's theses and special problems submitted to the University of the Philippines Institute of Library Science from 1990-1998. a total of 1265 citations were analyzed